Perbandingan Kewenangan Desa dalam Sistem Pemerintahan Pusat dan Daerah di Indonesia - Ramadani, Ramadani (Hukum tata Negara/Siyasah, 2024)
Abstract:This study aims to analyze and compare village authority in the central and regional government systems in Indonesia, especially after the enactment of Law Number 6 of 2014 concerning Villages. Through literature studies and policy analysis, this study reveals that the granting of autonomy to villages has provided a wider space for villages to manage their own government affairs. However, the implementation of village autonomy still faces various challenges, such as limited resources, capacity of village apparatus, and coordination between government levels. This study concludes that there needs to be a more systematic effort to strengthen village capacity, improve coordination between government levels, and provide adequate financial support so that village autonomy can run effectively. And Law Number 6 of 2014 concerning Villages has provided a breath of fresh air for village governments by providing a fairly wide range of autonomy. However, in practice, the implementation of village autonomy still faces various challenges, such as limited resources, capacity of village apparatus, and coordination between government levels. The village government system is the order or way of implementing government at the village level. This system is specifically regulated in the law, especially Law Number 6 of 2014 concerning Villages. The main purpose of this system is to give villages greater autonomy in managing their own government affairs and improve the welfare of the community at the village level.Abstrak:Penelitian ini bertujuan untuk menganalisis dan membandingkan kewenangan desa dalam sistem pemerintahan pusat dan daerah di Indonesia, khususnya setelah diberlakukannya Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Melalui studi literatur dan analisis kebijakan, penelitian ini mengungkap bahwa pemberian otonomi kepada desa telah memberikan ruang yang lebih luas bagi desa dalam mengelola urusan pemerintahannya sendiri. Namun, implementasi otonomi desa masih menghadapi berbagai tantangan, seperti keterbatasan sumber daya, kapasitas perangkat desa, dan koordinasi antar-tingkat pemerintahan. Penelitian ini menyimpulkan bahwa perlu adanya upaya yang lebih sistematis untuk memperkuat kapasitas desa, meningkatkan koordinasi antar-tingkat pemerintahan, serta memberikan dukungan finansial yang memadai agar otonomi desa dapat berjalan efektif. Dan Undang-Undang Nomor 6 Tahun 2014 tentang Desa telah memberikan angin segar bagi pemerintahan desa dengan memberikan otonomi yang cukup luas. Namun, dalam praktiknya, implementasi otonomi desa masih menghadapi berbagai tantangan, seperti keterbatasan sumber daya, kapasitas perangkat desa, dan koordinasi antar-tingkat pemerintahan. Sistem pemerintahan desa merupakan tatanan atau cara penyelenggaraan pemerintahan di tingkat desa. Sistem ini diatur secara khusus dalam undang-undang, terutama Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Tujuan utama dari sistem ini adalah memberikan otonomi yang lebih luas kepada desa dalam mengurus urusan pemerintahannya sendiri serta meningkatkan kesejahteraan masyarakat di tingkat desa.